Congenital midline cervical cleft - Ahmed Abdelghaffar Helal; Barakat Abdlreheem Mahmoud (Elsevier, 2018)
Congenital midline cervical cleft (CMCC) is a very rare congenital malformation of the neck. Although its embryologic origin is uncertain, the most widely accepted embryologic defect is impaired midline fusion of the distal branchial arches. We present a case of female child with this anomaly and review of relevant literature. In literature review, CMCC has been described almost exclusively in Caucasian Female, the present case documents the occurrence of this developmental anomaly in the Egypt populations. Key words: Congenital midline cervical cleft, Midline cervical anomalies, Branchial arch anomalies